Smart Analytics, Artificial Intelligence and Sustainable Performance Management in a Global Digitalised Economy - Tyagi, Pallavi (Emerald Publishing Limited, 2023)
The Covid 19 pandemic has created chaos in the business world and forced leaders to rethink their operational status quo. Though the benefits outweigh the risks, the challenges in digitalised economies are as sophisticated as the solutions they offer
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung